The Feasibility of Societal Cost Equivalence between Robotic Hysterectomy and Alternate Hysterectomy Methods for Endometrial Cancer - Neel T. Shah; Kelly N. Wright; Gudrun M. Jonsdottir; Selena Jorgensen; Jon I. Einarsson; Michael G. Muto (Hindawi Limited, 2011)
Objectives. We assess whether it is feasible for robotic hysterectomy for endometrial cancer to be less expensive to society than traditional laparoscopic hysterectomy or abdominal hysterectomy. Methods. We performed a retrospective cohort analysis of patient characteristics, operative times, complications, and hospital charges from all (𝑛=234) endometrial cancer patients who underwent hysterectomy in 2009 at our hospital. Per patient costs of each hysterectomy method were examined from the societal perspective. Sensitivity analysis and Monte Carlo simulation were performed using a cost-minimization model. Results. 40 (17.1%) of hysterectomies for endometrial cancer were robotic, 91 (38.9%), were abdominal, and 103 (44.0%) were laparoscopic. 96.3% of the variation in operative cost between patients was predicted by operative time (𝑅=0.963, 𝑃<0.01). Mean operative time for robotic hysterectomy was significantly longer than other methods (𝑃<0.01). Abdominal hysterectomy was consistently the most expensive while the traditional laparoscopic approach was consistently least expensive. The threshold in operative time that makes robotic hysterectomy cost equivalent to the abdominal approach is within the range of our experience. Conclusion. It is feasible for robotic hysterectomy to be less expensive than abdominal hysterectomy, but unlikely for robotic hysterectomy to be less expensive than traditional laparoscopy.